2010
DOI: 10.2147/dmso.s6935
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future: Critical analysis of use of gastric bands in obese patients

Abstract: Adjustable gastric banding (AGB) is quickly becoming the most popular bariatric operation performed in the United States and Canada. Patients are particularly fond of the simplicity of the tool, the relatively low morbidity of the surgery, the quick recovery, and overall results. The gastric band has evolved over its 35-year history into a very successful adjustable tool used to restrict food consumption and limit caloric intake. The percent of excessive weight loss after banding can range from 30%-60% and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
(118 reference statements)
1
9
0
2
Order By: Relevance
“…An overall devicerelated complication rate of 12-48% with a reoperation rate ranging from 10 -34% has been reported in the literature. 6 Other series have reported that 40 -50% of band recipients undergo additional surgery over the 10-year follow-up period. 1,5 Aarts et al 12 published a study of 201 patients who underwent LAGB, of which 53% had the band removed or converted to another bariatric surgery approach because of insufficient weight loss or complications.…”
Section: Erosion Of Gastricmentioning
confidence: 97%
See 3 more Smart Citations
“…An overall devicerelated complication rate of 12-48% with a reoperation rate ranging from 10 -34% has been reported in the literature. 6 Other series have reported that 40 -50% of band recipients undergo additional surgery over the 10-year follow-up period. 1,5 Aarts et al 12 published a study of 201 patients who underwent LAGB, of which 53% had the band removed or converted to another bariatric surgery approach because of insufficient weight loss or complications.…”
Section: Erosion Of Gastricmentioning
confidence: 97%
“…11 Various studies reviewing the long-term outcomes up to 10 -15 years after LAGB demonstrate disappointing excess weight loss, weight regain, and reappearance of obesity-related conditions. Snyder et al 6 showed that the failure to achieve a satisfactory excessive weight loss in the first several years after surgery range from 10 -20% with an even greater failure rate occurring when evaluated long-term. Likewise, multiple studies have reported better long-term weight loss and resolution of comorbidities with other bariatric procedures 6,7 when compared to LAGB.…”
Section: Erosion Of Gastricmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 In our institution, it is the most commonly performed bariatric procedure. 6,7 However, LAGB and other purely restrictive operations result in lower-than-expected average weight loss, higher weight regain and less resolution of comorbidities, compared to malabsorptive surgical procedures, exemplified by gastric bypass and biliopancreatic diversion (BPD).…”
Section: Introductionmentioning
confidence: 99%